Legal Considerations of Domestic Violence in Divorce (Case study at the Merauke Religious Court No. 254 / Pdt.G / 2022 / PA. Mrk) - Suwarno, Suwarno; Yulia Rahman, Hendra; Al Abza, M.Thohar (International Journal of Sustainable Law, 2024)
Violence in Rmah Tangga (KDRT) is one of the reasons that is often used as the basis for divorce applications in court. This study aims to analyze the legal considerations desired by the judges of the Merauke Religious Court in deciding divorce cases on the basis of domestic violence in decision Number 254/Pdt.G/2022/PA.M. This research uses qualitative research methods. By using an empirical study or case study approach. The data collection is sourced from the results of the decision of case Number 254/Pdt.G/2022/PA. Mrk and interview. The results of the study indicated that case Number 254/Pdt.G/2022/PA. The reason that makes the plaintiff in this case the wife filed for divorce from the defendant who is none other than her husband is the first physical violence. The plaintiff said that this physical violence was in the form of beating and kicking the plaintiff which had an impact on bruises on his body. The second reason for the plaintiff is the existence of Psychological Violence, namely the defendant always says rude words that cause fear and threats to the plaintiff. The subsequent finding is that case Number 254/Pdt.G/2022/PA. Mrk mentioned that the judge in considering the filing of divorce on the grounds of Syiqaq or the existence of continuous quarrels and disputes. These legal considerations certainly obscure the reasons put forward by the plaintiff under the pretext of domestic violence, namely the existence of physical and psychological violence. In general, of course, the judge in considering the law in the decision has been fair, that is, the judge is based on benefits. Which if this case is not granted, it will cause great benefits or harm to one of the parties.